Evaluation of leaching potential of tebuthiuron using bioindicator plants - Silva Junior, Antonio Carlos Da; Gonçalves, Clebson Gomes; Queiroz, Juliana Roberta Gobi; Martins, Dagoberto (Instituto Biológico, 2018)
ABSTRACT: The last destination of most herbicides used in agricultural systems is the soil. This is a dynamic interaction; herbicides can remain in the soil solution or be carried through the soil profile, reaching the water table. The objective of this work was to evaluate the leaching potential of the tebuthiuron herbicide using bioindicator plants grown in an Oxisol of sandy loam texture and in an Entisol of clay texture, after the occurrence of natural rainfall events. A complete randomized experimental design was used, in a 3×8 factorial arrangement, with four replications. The treatments consisted of three accumulated natural rainfall depths (30-40, 60-80, and 100-120 mm) and eight soil profile layers (0-3, 3-6, 6-9, 9-12, 12-15, 15-20, 20-25, and 25-30 cm). Soil samples were collected after the tebuthiuron herbicide application - 750 for clayey soil, and 600 g ha-1 for the sandy loam soil -and the rainfall events. PVC pipes with length of 30 cm and diameter of 15 cm were introduced into the soil profile for sampling. The pipes with soil columns were carefully removed by digging around them, to maintain the soil original integrity during collection and, subsequently, cut longitudinally for sowing the bioindicator species - cucumber (Cucumis sativus L.), and lettuce (Lactuca sativa L.). Then, the phytotoxicity in the bioindicator plants grown in these soils were evaluated at 5, 7, 10, and 12 days after sowing, using a grading scale of 0 to 100%. The mobility of the tebuthiuron herbicide was low in both soils, regardless of the rainfall depth, and the cucumber was the most suitable plant species to use as a bioindicator.

RESUMO: O solo é o destino final da maioria dos herbicidas utilizados no sistema agrícola e, sendo esta relação dinâmica, eles podem permanecer na solução ou ser carregados no perfil do solo, podendo atingir o lençol freático. O objetivo deste trabalho foi avaliar o potencial de lixiviação do herbicida tebuthiuron por meio de plantas bioindicadoras e após a ocorrência de precipitações pluviométricas naturais, em solos com texturas franco arenoso (Latossolo Vermelho-Amarelo) e argiloso (Neossolo Litólico). O delineamento experimental foi o inteiramente casualizado em um esquema fatorial 3 x 8 com quatro repetições, sendo três níveis de precipitação pluviométrica (30-40, 60-80 e 100-120 mm) e oito de profundidade do perfil do solo (0-3, 3-6, 6-9, 9-12, 12-15, 15-20, 20-25 e 25-30 cm). As coletas das amostras ocorreram após a aplicação do herbicida tebuthiuron nas doses de 750 e 600 g ha-1 para o solo argiloso e arenoso, respectivamente, e posterior acúmulo das precipitações. Para a coleta das amostras foram introduzidas, no perfil do solo, colunas de PVC com 30 cm de altura e 15 cm de diâmetro. As colunas foram retiradas cuidadosamente escavando-se ao seu redor, mantendo a integridade original do solo durante a coleta. Posteriormente, as colunas foram separadas com corte longitudinal, para a semeadura das espécies bioindicadoras pepino (Cucumis sativus L.) e alface (Lactuca sativa L.). Para as avaliações das plantas bioindicadoras nas colunas, adotou-se a escala de notas de 0 a 100% de fitotoxicidade, aos 5, 7, 10 e 12 dias após a semeadura. A mobilidade do herbicida tebuthiuron mostrou-se reduzida em ambos os tipos de solo estudado, independentemente da precipitação pluvial, e as plantas de pepino mostraram-se mais adequadas para serem utilizadas como espécie bioindicadora.
Estudo da lixiviação do herbicida tebuthiuron com plantas bioindicadoras
Keywords: Herbicide dynamics; soil profile; soil class; weeds; Dinâmica de herbicidas; perfil do solo; tipo de solo; plantas daninhas